Nivolumab-Induced Periaortitis Demonstrated by FDG PET/CT. (November 2020) - Hotta, Masatoshi; Naka, Go; Minamimoto, Ryogo; Takeda, Yuichiro; Hojo, Masayuki
Abstract : Abstract: A 66-year-old man with a history of non–small cell lung cancer treated with nivolumab underwent contrast-enhanced CT and FDG PET/CT. No recurrence was demonstrated; however, soft-tissue thickening that showed delayed contrast enhancement and FDG uptake was detected around an abdominal aortic aneurysm. After discontinuation of nivolumab, the periaortic lesion disappeared within 2 months, indicating nivolumab-induced periaortitis. Immune checkpoint inhibitors such as nivolumab can cause vasculitis and periaortitis, a potentially fatal condition, as immune-related adverse events. The underlying aortic aneurysm may have contributed to genesis of periaortitis. FDG PET/CT can be useful for detecting periaortitis and excluding other forms of vasculitis.